Adaptation of Geomatics Engineering Teacher of Dual Expertise Program to New Skill Competencies - David Yavis; Nanang Dalil Herman (INVOTEC, 2022)
Research on eleven participants who work as teachers of the Geomatics Engineering Dual Expertise Program spread across various provinces throughout Indonesia has provided an in-depth desciption of the adaptation process they experienced to their new competency skills. The author conducts interviews with video calls through applications on sosial media by giving several questions to participants and also asking participants to tell about the adaptation process they have experienced so that the results obtained from this interview are more in-depth. The author processes the research data by transcribing the document, compressing the facts, then coding so that the conclusion is in the form of certain themes that can be grouped. From this research, the authors have succeeded in describing the main obstacles experienced by teachers in adapting and how they can overcome these obstacles in their way. This research shows that some of the obstacles for the geomatics engineering dual expertise program teacher in adapting to this skill competency are understanding new subject matter in the competency of geomatics engineering expertise, namely Geographic Information Systems (GIS) and Remote Sensing (RS) which are closely related to learning using software certainly. Inadequate facilities and infrastructure such as practical equipment for teaching and learning activities, lack of support from senior teachers in schools. The participants tried to overcome the obstacles they experienced with the shocking reality because they avoided teaching difficult subjects (subjects in Grade XI and XII) or tried to gain knowledge with senior teachers in school, even though not all senior teachers can provide support due to limited understanding of new material.